Item Analysis of Arabic Thematic Questions to Determine Thinking Level Ability - Kadir, Suleman; Sarif, Suharia; Fuadi, Abdul Hafizh Nur (Language Development Center, 2024)
Background: Thematic Arabic language test items are crucial to be analyzed, but the interesting aspect is to determine whether the Arabic language questions used meet the criteria of HOTS (High Order Thinking Skill) questions. Purpose: To analyze HOTS (High Order Thinking Skills)-based thematic Arabic language questions, which involves the analysis of test items that meet the criteria and possess high-level thinking skills. Method: This research employs a mixed-method approach, combining qualitative and quantitative methods, as the analysis in this research requires examination from these two perspectives to generate accurate verbal and numerical results. The research sample consisted of 101 individuals from 3 classes. Data collection was conducted by distributing the test items to the students and analyzing them using the Anates application.. Results and Discussion: The analysis results show that the existing test items still contain a low level of LOTS (Low Order Thinking Skill) thinking, therefore improvements and revisions are necessary so that they can be re-tested in the next stage. Specifically, based on the analysis, there are several questions that still fall into the C3 criteria (items 6 and 15), C2 (item 14), and C1 (items 7-12). Meanwhile, in terms of quality, as measured through the Anates application, the XY correlation has a value of 0.63, the test score reliability is 0.78, and the difficulty level is found in items 2, 14, 11, and 15, which still need to be corrected and revised. Conclusions and Implications: The thematic questions that have been tested meet the HOTS criteria, but in terms of quality, they are still relatively moderate, with some questions leaning towards LOTS, therefore requiring revisions. Research Implications: The findings of this study can be used as a reference for educators to design and analyze HOTS-based questions in Arabic language learning, particularly in relation to the enhancement of students' higher-order thinking skills. These results can also encourage the development of more comprehensive assessment instruments that align with the current curricular demands.